Study on thermal performance of Precast Concrete Sandwich Panel (PCSP) design for sustainable built environment - Soon Ern, Peniel Ang; Mei Ling, Lim (Penerbit Uthm, 2018)
Sustainability in construction industry has become an issue when designing a new building [1] and the conventional on-site construction methods have long been criticised for imposing rigorous human health and safety risk, as well as causing significant environmental destruction [2]. Meanwhile, PCSP can be perceived as an alternative approaches in creating and maintaining the sustainable built environment. Finsen & Georgia (2011) [1] said that this wall system can maximise benefits from integrated strategies, which focus on all of the building’s materials and systems, as well as the way they interact.